Longhorn beetles (Coleoptera: Cerambycidae) of northeastern India: An Overview - Behere, G. T.; Firake, D. M.; Thubru, D. P.; Burange, P. S.; Ngachan, S. V. (Indian Journal of Hill Farming, 2018)
The northeastern (NE) region of the India is a part of mega biodiversity hotspot and represents one of the highest floral and faunal biodiversity of the Indian subcontinent. The longhorn beetles or cerambycid beetles are important pest of vegetable, fruit and forest trees. In this study, more than 580 beetle (adult) specimens were collected from diverse agricultural, horticultural, and forest ecosystems of eight states of northeastern India during 2013 to 2016. Out of 95 different taxons collected, 62 taxons were identified up to species level and 19 taxons were identified up to genus level. The details on collection, distribution, activity period, host plants or habitat have been mentioned in this report. This study will certainly be helpful to the researchers, students, state government agencies and biodiversity personnel working in this area